Anti-inflammatory effects of vagus nerve stimulation in pediatric patients with epilepsy - Kaur, Supender; Selden, Nathan R.; Aballay, Alejandro (Frontiers in Immunology, 2023)
The neural control of the immune system by the nervous system is critical to maintaining immune homeostasis, whose disruption may be an underlying cause of several diseases, including cancer, multiple sclerosis, rheumatoid arthritis, and Alzheimer’s disease. Here we studied the role of vagus nerve stimulation (VNS) on gene expression in peripheral blood mononuclear cells (PBMCs). Vagus nerve stimulation is widely used as an alternative treatment for drug-resistant epilepsy. Thus, we studied the impact that VNS treatment has on PBMCs isolated from a cohort of existing patients with medically refractory epilepsy. Comparison of genome-wide changes in expression between the epilepsy patients treated and non-treated with vagal stimulation showed downregulation of genes related to stress, inflammatory response, and immunity, suggesting an anti-inflammatory effect of vagus nerve stimulation in epilepsy patients. VNS also resulted in the downregulation of the insulin catabolic process, which may reduce circulating blood glucose. These results provide a molecular explanation for the beneficial role of the ketogenic diet, which also controls blood glucose, in the treatment of refractory epilepsy. The findings indicate that direct vagus nerve stimulation might be a useful therapeutic alternative to treat chronic inflammatory conditions.